Organic compounds in vent fluids from Yellowstone Lake, Wyoming. (September 2021) - Ong, Claire; Fowler, Andrew P.G.; Seyfried, William E.; Sun, Tao; Fu, Qi
Highlights: Organic compounds in vent fluids from SI Deep Hole and West Thumb, Yellowstone Lake. Diverse structural complexities and relative quantities of organic molecules. Fluid-rock interactions under physicochemical conditions key to organic formation. Involvement of magmatic degassing and microbial activity for dissolved CO2 and CH4 . Interplay of geological, chemical and biological processes in Yellowstone ecosystem. Abstract: Hydrothermal fluids were collected over a three-year interval (2016–2018) from two sublacustrine vent fields in Yellowstone Lake, Wyoming: Stevenson Island Deep Hole (YL16 and YL17 series in 2016 and 2017, respectively) and West Thumb (YL18 series in 2018). The TOC content in SI Deep Hole vent fluids varies from 2.7 mg/L to 6.3 mg/L in YL16 and 5.0 mg/L to 16.2 mg/L in YL17. Compared to YL16, the average TOC value of YL17 has more than doubled. The range of TOC is from 7.3 mg/L to 13.7 mg/L in the West Thumb samples. A positive correlation between TOC and dissolved CO2 concentration is observed in most samples, suggesting their close relationship with sublacustrine heat and mass transfer processes. The organic compounds detected at both vent fields are diverse in molecular structure. In the SI Deep Hole, complex cyclic and unsaturated organic compounds are dominant, with cyclic hydrocarbons having the highest abundance, followed by carboxylic acids, PAHs, and alcohols. At West Thumb vents, propanol is most abundant, followed by alcohols, PAHs, alkanes, and carboxylic acids. This difference in structural complexity and relative quantity of organic compounds may be attributed to the involvement of hydrothermal processes. The vapor-dominated hydrothermal system and extensive fluid-rock interactions in SI Deep Hole facilitate alteration/decomposition of organic precursors. While CO2(aq) is predominant in vent fluids, dissolved CH4 is much less abundant. In SI Deep Hole, the carbon isotopic composition of CH4 in most samples ranges from −20.4‰ to −38.0‰, with values of less than −60‰ in three samples, while CO2 ranges from −4.4‰ to −10.5‰. A temporal variation of δ 13 C values was obtained for CO2, with the average increasing from −9.2‰ (YL16) to −5.2‰ (YL17). In West Thumb, the δ 13 C value of CO2 and CH4 fall in a similar range, with an average of −10.5‰ and −19.0‰, respectively. There are multiple sources for observed carbon species: the interaction of vent fluids with subsurface rocks and lake sediments is the predominant process, followed by thermal decomposition of organic matter. Microbial activity on the lake floor may contribute to methane formation, while magmatic degassing is the major process that produces CO2 . The connection between vapor-dominated hydrothermal alteration, elevated TOC contents and dissolved CO2 in vent fluids, and enrichment of 13 C in CO2 in YL17 in SI Deep Hole suggests an interplay of geological, chemical, and biological processes and their imprints on vent fluids, all of which make significant contribution to the carbon cycle in the Yellowstone Lake ecosystem.